Production of goat offspring from in vivo-derived embryos through embryo transfer technique / Xiao Zhi Chao - Xiao, Zhi Chao (2013)
Goat emAbryo transfer is an important tool to improve the genetics and to increase rapidly the number of economically superior goat for the industry. The objective of this study was to develop a suitable protocol for the collection and transfer of goat embryos as well as subsequently to produce goat kids through embryo transfer. Two different hormones (PMSG, FSH-V), two different localities (Kuala Lumpur, Malaysia and Kunming, China) and the embryo recovery cycle were designed to evaluate the ovarian responses and embryo transfer performance. For donor goats, the treatment was 14 or 17 days CIDR and before CIDR withdrawal, 1200 IU PMSG or 160 mg FSH-V were injected before CIDR withdrawal, and then followed by checking oestrus and natural mating. After day-7 CIDR withdrawal, uterine horn was flushed surgically to collect embryos. For recipient goats, similar CIDR administration was given and upon CIDR withdrawal, 300 IU PMSG was injected. On the same day, the collected embryos were transferred into the uterus of the recipient, in which it was confirmed by appearance of 1 to 2 corpus luteum on the ovaries. A total of 460 embryos were obtained from 122 donor does, out of which 174 embryos were transferred to 117 recipient does, resulting in the delivery of 73 kids in Kunming and 3 kids in Kuala Lumpur. Both donor and recipient does synchronised with 17 days of CIDR administration showed a higher ovulation rate compared with 14 days of CIDR treatment with the values of 90 and 67%, respectively. The ovulation and unfertilised oocytes plus embryos recovery rates were higher in the FSH-V (100 and 44%, respectively) than those of PMSG treated does (95 and 34%, respectively). The FSH-V treatment gave better results than PMSG treatment in both fertilisation rate (43.55% vs. 34.08%, respectively) and number of embryos ii obtained (4.38±0.85 vs. 0.63±0.23, respectively). The ovarian responses and embryo transfer performances after FSH-V treatment were better in Kunming than in Kuala Lumpur (unfertilised oocytes plus embryos: 9.47±0.64 vs. 5.06±0.90; number of embryos obtained: 8.13±0.69 vs. 4.38±0.85; the pregnancy rate: 65.69 vs. 11.11%; kidding rate: 71.57 vs.0%, respectively). The total number of embryos recovered after superovulation of first (116 embryos) and second (80 embryos) flushing cycles were higher than third (4 embryos) flushing cycle. It is concluded that superovulation using specific hormones protocol and localities as well as the superovulation cycles are important factors for consideration in embryo transfer programme of goats.